Antithrombotic and anticoagulation therapies in cardiogenic shock: a critical review of the published literature. (19th October 2021) - Radu, Razvan I.; Ben Gal, Tuvia; Abdelhamid, Magdy; Antohi, Elena‐Laura; Adamo, Marianna; Ambrosy, Andrew P.; Geavlete, Oliviana; Lopatin, Yuri; Lyon, Alexander; Miro, Oscar; Metra, Marco; Parissis, John; et al.
Abstract: Cardiogenic shock (CS) is a complex multifactorial clinical syndrome, developing as a continuum, and progressing from the initial insult (underlying cause) to the subsequent occurrence of organ failure and death. There is a large phenotypic variability in CS, as a result of the diverse aetiologies, pathogenetic mechanisms, haemodynamics, and stages of severity. Although early revascularization remains the most important intervention for CS in settings of acute myocardial infarction, the administration of timely and effective antithrombotic therapy is critical to improving outcomes in these patients. In addition, other clinical settings or non‐acute myocardial infarction aetiologies, associated with high thrombotic risk, may require specific regimens of short‐term or long‐term antithrombotic therapy. In CS, altered tissue perfusion, inflammation, and multi‐organ dysfunction induce unpredictable alterations to antithrombotic drugs' pharmacokinetics and pharmacodynamics. Other interventions used in the management of CS, such as mechanical circulatory support, renal replacement therapies, or targeted temperature management, influence both thrombotic and bleeding risks and may require specific antithrombotic strategies. In order to optimize safety and efficacy of these therapies in CS, antithrombotic management should be more adapted to CS clinical scenario or specific device, with individualized antithrombotic regimens in terms of type of treatment, dose, and duration. In addition, patients with CS require a close and appropriate monitoring of antithrombotic therapies to safely balance the increased risk of bleeding and thrombosis.